2019
DOI: 10.4103/bc.bc_52_19
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin-actin rod formation in experimental stroke is attenuated by therapeutic hypothermia and overexpression of the inducible 70 kD inducible heat shock protein (Hsp70)

Abstract: Cofilin-actin rod formation in experimental stroke is attenuated by therapeutic hypothermia and overexpression of the inducible 70 kD inducible heat shock protein (Hsp70).Permalink https://escholarship.org/uc/item/2qb082g3 Journal Brain circulation, 5(4) Abstract:BACKGROUND AND PURPOSE: Cofilin-actin rods are covalently linked aggregates of cofilin-1 and actin. Under ischemic conditions, these rods have been observed in neuronal dendrites and axons and may contribute to the loss of these processes. Hypother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Ischemia also leads to loss of dendrites and spines in neurons, even with survival of the parent cell body ( Tanay et al, 2006 ). Cofilin-actin rod suppression during the acute phase of ischemic stroke might provide neuroprotection with histological results ( Kurisu et al, 2019 ). It has also been reported that cofilin-1 increases in oxygen glucose deprivation model of ischemia with in vitro fetal mouse neurons ( Madineni et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia also leads to loss of dendrites and spines in neurons, even with survival of the parent cell body ( Tanay et al, 2006 ). Cofilin-actin rod suppression during the acute phase of ischemic stroke might provide neuroprotection with histological results ( Kurisu et al, 2019 ). It has also been reported that cofilin-1 increases in oxygen glucose deprivation model of ischemia with in vitro fetal mouse neurons ( Madineni et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HSP70-deficient mice exhibited an increased cofilin-actin rod and a larger lesion size in the ischemic border zone. In contrast, HSP70 overexpression in transgenic mice reduced rod formation and improved neurological symptoms following stroke [ 128 ]. These reports indicate that cofilin is necessary during the recovery phase of stroke, and perturbed cofilin activity during this period might negatively affect the regenerative process.…”
Section: Cofilin Dysregulation and Neurodegenerative And Psychiatric Disordersmentioning
confidence: 99%
“…В то же время не менее доказательный экспериментальный материал демонстрирует обратное [40]. Есть основания предполагать, что экспрессия БТШ при гипотермии провоцируется не понижением температуры, а ее повышением в период согревания после охлаждения, и может происходить при значительно сниженных температурах [41,42]. Предполагают, что согревание после охлаждения активирует клеточное дыхание, кровоток и образование свободных радикалов в тканях, что формирует сигналы экспрессии ранних генов.…”
Section: молекулярные механизмы низкотемпературных технологийunclassified